2010
DOI: 10.1097/bsd.0b013e3181d0c1e5
|View full text |Cite
|
Sign up to set email alerts
|

Total Spondylectomy of C2

Abstract: Preservation of bilateral vertebral arteries and all cervical nerve roots is feasible when carrying out intralesional total spondylectomy in patients with C2 vertebral body tumors and should be considered in patients thought to benefit from total C2 vertebra excision. In an attempt to augment construct stability and provide anterior column load sharing, we have used mesh cage and iliac crest graft between C1 and C3 held in place with a short cervical plate without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
0
9
0
13
Order By: Relevance
“…It has been shown that conducting the posterior operation first can reduce the risk of failure of column support and VA injury. [ 14 ] In the first case, we performed the posterior laminectomy first because this can enlarge the vertebral canal volume and increase the mobility of the cervical cord, thereby reducing the risk of spinal cord injury during the anterior operation. Although conducting the posterior surgery first can reduce the risk of implant migration and VA injury, it can make the anterior operation difficult, especially in the high cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that conducting the posterior operation first can reduce the risk of failure of column support and VA injury. [ 14 ] In the first case, we performed the posterior laminectomy first because this can enlarge the vertebral canal volume and increase the mobility of the cervical cord, thereby reducing the risk of spinal cord injury during the anterior operation. Although conducting the posterior surgery first can reduce the risk of implant migration and VA injury, it can make the anterior operation difficult, especially in the high cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…Expected dysphagia and upper airway problems may lead to the need for gastrostomy, tracheostomy or both. 6 Furthermore, the anterior instrumentation is in close proximity to the pharynx. This is particularly concerning because retropharyngeal instrumentation carries the risk of hardware exposure in patients who receive radiation and/or are malnourished due to systemic disease and/or dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Axial spondylectomy can be done with combined anterior and posterior incisions with preservation of all neurovascular structures, as advocated by some. 6,31 However, preservation of the rostral cervical nerve roots is not necessary, with many surgeons advocating their routine sacrifice in atlantoaxial fusion. Indeed, a recent large case series demonstrates that C2 neurectomy is benign and facilitates exposure as well.…”
Section: Discussionmentioning
confidence: 99%
“…Chirurgická léčba je velice obtížná. Naději na vyléčení má jedině kompletní "en bloc" exstirpace se širokými okraji zdravé tkáně (2,16,26,32,34), bez poškození pseudopouzdra, co je těžké dodržet při postižení mobilní páteře, kde nesmíme poškodit míchu a zachovat nervové kořeny. 20) uvádějí lokální recidivu u pacientů s en bloc resekcí ve 28 %, kdežto u pacientů kde bylo porušené pouzdro v 64 %.…”
Section: Diskuseunclassified